Evaluation of malaria risk factors prevention and control program in Kulon Progo Regency - Husni Husni; Th. B Rahayujati; S Supargiyono (Berita Kedokteran Masyarakat (BKM), 2017)
Evaluation of malaria risk factors prevention and control program in Kulon Progo RegencyPurposeThe purpose of this research was to evaluate the program of prevention and control of malaria risk factors in Kulon Progo District in 2016 based on system approach.MethodThis research was evaluation program used mixed methods (sequential explanatory design). Data collected from 7 public health center of active focus malaria and district health office. Respondents were program managers and head of public health center, district program managers, head of control and eradication of communicable diseases, and head of district health offices. The instruments used structured questionnaires and in-depth interview guides. Quantitative data analysis was descriptive and qualitative data used Miles and Huberman model.Results Most of the availability of human resources, funds, facilities, materials, and methods already meet implementation needs except entomologists, allocation of funds activities other than IRS, time of the implementation of larval fish deployment. Most of the processes that started from the planning, implementation, monitoring, and evaluation have gone well except for planning other than IRS, preparation vector control without entomology database, implementation of environmental management, larviciding, and larval fish deployment. Coverage of LLINs, coverage of IRS, control of LLINs efficacy, and test of vector resistance have met the target, except coverage of larviciding and larval fish deployment was not available.ConclusionPrevention and control program of malaria risk factors has implemented but wasn’t based on entomological data. District health offices should recruit entomologist to support vector control activities.